Biomechanics of staircase exercises / Almashaqbeh Sami Faris - Almashaqbeh, Sami Faris (2010)
Exercises provide many important health benefit to individuals. People should therefore be encouraged to change their life style by including some kinds of physical activities into their daily routines. A staircase provides free and easy access as a tool for exercising. A wide variety of exercises has been proposed to be done on a staircase. Among them are walking up and down stairs ' with the hands behind the head, walking holding dumbbells, walking in cross-step manner, and lateral stepping. The joint-specific differences in the kinematics and kinetics patterns between such exercises and regular stair climbing may be used to target specific muscle groups of the lower extremity. On the other hand, the increase in weight associated with obesity is supp d to directly increase the knee load that subsequently leads to the development of knee o teoarthriti . Activities place greater demands on the hip exten or , and that the h !ding dumbbells activity places greater demand on the knee exten rs and on the ankle dorsitlexors. In the frontal plane, the cro step forward and the lateral tepping (leading limb during descent and trailing limb during a cent) activitie place greater demands on the hip abductors, and that the cross tep forward and the lateral stepping (trailing limb during descent) activities place greater demands the knee abductors. These findings can be used to more effectively target specific lower-extremity muscle groups when recommending exercise for young individuals. Obese individuals might adjust t their gait characteristics in response to their heavy bodies to reduce or maintain the same load on the knee joint as the slim people. Therefore, obese people can safely perform the selected exercise.